2017
DOI: 10.1093/jac/dkx414
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of a clinical microbiology service at a Cambodian paediatric hospital and its impact on appropriate antimicrobial prescribing

Abstract: BackgroundAntimicrobial resistance threatens human health worldwide. Antimicrobial misuse is a major driver of resistance. Promoting appropriate antimicrobial use requires an understanding of how clinical microbiology services are utilized, particularly in resource-limited settings.ObjectivesTo assess the appropriateness of antimicrobial prescribing and the factors affecting utilization of the established clinical microbiology service (CMS). The CMS comprises the microbiology laboratory, clinical microbiologis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…Our study illustrates the challenges associated with providing care for children who have melioidosis at a pediatric hospital in northern Cambodia. Unlike many hospitals in the region, there was access to level 3 care in a pediatric intensive care unit and an on-site diagnostic microbiology laboratory supported by an active clinical microbiology liaison service ( 10 ). Nevertheless, 2/10 children admitted because they had melioidosis did not survive to leave the hospital, and only one third of those discharged alive were confirmed as having completed eradication therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Our study illustrates the challenges associated with providing care for children who have melioidosis at a pediatric hospital in northern Cambodia. Unlike many hospitals in the region, there was access to level 3 care in a pediatric intensive care unit and an on-site diagnostic microbiology laboratory supported by an active clinical microbiology liaison service ( 10 ). Nevertheless, 2/10 children admitted because they had melioidosis did not survive to leave the hospital, and only one third of those discharged alive were confirmed as having completed eradication therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical decision-making is not only influenced by guidelines and operational constraints; the social determinants of prescribing must be understood in order to effect a change in practice [ 28 ]. Hierarchy and peer pressures shaped antibiotic prescribing decisions in our study, as in other settings [ 26 ], but these influences have not previously been explored in Africa, where qualitative studies of stewardship have focused on nursing behaviors [ 24 , 25 ] and general perceptions of AMR [ 29 ]. More in-depth social research should be undertaken to provide a deeper understanding of the mechanisms for changing behavior, if large-scale programs are to be successful.…”
Section: Discussionmentioning
confidence: 99%
“…Doctors indicated that access to better microbiology services would reduce their use of empirical antibiotics, similar to surveys conducted in Cambodia, but indicated that, even with an identified respiratory virus, they would still provide antibiotics given concerns about bacterial co‐infection. Antibiotic stewardship programmes should reduce antibiotic use, while access to better microbiology services in Cambodia and rapid influenza tests in Sri Lanka have been associated with a significant decrease in antibiotic prescriptions. A recent randomised controlled trial study in Vietnam demonstrated that a point‐of‐care C‐reactive protein test can safely reduce unnecessary antibiotic use in children with an acute respiratory infection .…”
Section: Discussionmentioning
confidence: 99%